WOMEN IN THE DIGITAL AGE: A QUR’ANIC ETHICAL CRITIQUE OF GLOBAL BEAUTY CULTURE - Gustianda, Nana; Hidayat, Rahmad; Yuliani, Tri; Marlina, Inda; Adhli, Aulya; Maryani, Wela (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2025)
The purpose of this study is to critically review the global beauty culture towards women in the digital era from the perspective of Qur'anic ethics, representing several female figures in the Qur'an as role models who demonstrate that the value of humanity and the virtue of women are determined by moral integrity, social roles, and steadfast faith, not solely by standards of physical beautyAlthough research on the representation of women's bodies in digital media is growing, there is still a lack of research that connects with ethical principles in the Qur'an, especially in the context of internalized beauty standards. This study uses a qualitative method with a comparative analysis approach. The study focuses on comparing the phenomenon of beauty construction that has developed on social media with the Qur'an's perspective on the position of humans. The results of this study show that the Qur'an gives an overview of beauty is not about the shape of the face or body, but the balance between inner and outer, ethics in appearance, and self-awareness before God. This is in stark contrast to digital culture that standardizes beauty narrowly, often reducing women to visual objects.